La revolución de 1854 en el Perú. Moralidad, honor y contrato social - Aljovín de Losada, Cristóbal; Velásquez Silva, David (Anuario de Historia de América Latina, 2021)
This article seeks to understand the meaning that the historical actors gave to the Revolution of 1854. The speeches and actions of its protagonists were built and changed throughout the political struggle. There were different discursive frameworks to define the government and the revolution. These arguments and actions obeyed republican and pactist imaginaries, but also liberal ideology. Through the political struggle (military, electoral and discursive), the changing character of this revolution was outlined for the various actors, not without ambiguities and alternative visions.